The enigmatic genus Ctenostylum Macquart with the description of a new species from the Brazilian Amazon Basin and a checklist of world Ctenostylidae species (Diptera) - Rafael, José Albertino; de Jesus Pimentel, Therezinha; Godoi, Fabio Siqueira P.; Machado, Renato Jose Pires (Zootaxa, 2009)
The genus Ctenostylum Macquart, 1851 was known only from two male specimens, one from Brazil and one from Costa Rica. Ctenostylum fuscomaculatum n. sp., is described based in one female specimen collected in the Amazon Basin, the third specimen known. The diagnosis of the genus Ctenostylum is redefined and its relationships with other ctenostylid genera are discussed.